Leverage, Maturities of Debt and Stock Performance (International Journal of Banking and Finance, 2013)
We add to the prior literature that test the influence of total leverage on stock returns by focusing on an extended ratio, namely, â€˜Total Debt to (Total Capital + Long Term Debt)â€™, TD/(TC+LTD)â€™, the ratio henceforth. Further, and in contrast with others, we account for different maturities of debt. The link between this ratio and stock returns for periods of one to sixty months are considered for Germany, the UK and the US. We control for beta and form quintiles based on the ratio to compute mean returns. Our findings indicate a robust negative relation between the ratio and returns for Germany and the UK. In these two markets, the lowest ratio-quintile performs better that the highest ratio-quintile for all the periods studied. Interestingly, the results for the United States are less clear. Due to a number of known factors, market efficiency might be higher in the US than in the other two markets.